Religion and the Recovery of Addicted Women - Turner, Norma Haston (Journal of religion and health, 1999)
Personal interviews were conducted with 102 African-American and Anglo-American women in Texas coastal communities to determine the involvement of religious organizations in women's initiation and maintenance of recovery from drug addiction, the extent of women's help-seeking for recovery, and women's spiritual needs. Means, frequencies, chi squares, Pearson's correlations, and one-way ANOVAs were used to describe the data. Religious organizations helped about one-third of the women to begin or stay in recovery, primarily through counseling or ministering to spiritual needs. Only one-fourth of the women had sought help from churches. The predominant spiritual needs were forgiveness, love, and understanding. Implications for research and outreach are given.